2014
DOI: 10.1177/0969141314542667
|View full text |Cite
|
Sign up to set email alerts
|

A whole-population profile of HPV testing as a test of cure for high-grade cervical dysplasia in NSW, Australia

Abstract: Introduction: Few population-based studies have been conducted on the efficacy of human papilloma virus (HPV) testing as a test of cure for high grade cervical dysplasia. Methods: A cohort of women (n ¼ 11,521) with high grade (CIN2þ) cervical dysplasia diagnosed during 2006-2010, who also had accompanying HPV testing (n ¼ 19,434 HPV tests), was analyzed with respect to National Health and Medical Research Council (NHMRC) follow-up guidelines. Cure rates, and number of follow-up tests and times to reach a cure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…The results here indicate that an overall low ToC completion rate is similar to findings recently reported in a New South Wales retrospective study . As reported by Morrell and Qian, it is possible that general practitioners and other women's health clinicians believe that a single HR HPV‐negative test result, along with successive negative cytology, is sufficient to indicate successful treatment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results here indicate that an overall low ToC completion rate is similar to findings recently reported in a New South Wales retrospective study . As reported by Morrell and Qian, it is possible that general practitioners and other women's health clinicians believe that a single HR HPV‐negative test result, along with successive negative cytology, is sufficient to indicate successful treatment.…”
Section: Discussionsupporting
confidence: 87%
“…This management pathway returns eligible women back to routine screening (two yearly) and reduces previously required post‐treatment surveillance frequency . Multiple follow‐up studies have shown HR HPV testing to be efficacious for detecting residual or recurrent disease inpatients treated for HSIL …”
Section: Introductionmentioning
confidence: 99%
“…For example, in England, HPV testing is used to triage cytology tests showing borderline changes or low-grade dyskariosis, reducing the number of women on early recall, and speeding up colposcopy follow-up for those with high-risk HPV (Kelly et al, 2011;Kitchener et al, 2009). In the UK and Australia, HPV testing is also used as a 'test of cure' for treatment of cervical abnormalities, allowing women to return to regular screening if no high-risk HPV infection is detected (Kitchener et al, 2008;Kitchener et al, 2013;Morrell & Qian, 2014). The UK NHS cervical screening programme will change to HPV primary testing in 2019 (Rebolj et al, 2019).…”
Section: Introductionmentioning
confidence: 99%